Perancangan Multimedia Informasi Iklan Layanan Masyarakat “Domestic Abuse” Di Dinas Pemberdayaan Perempuan Perlindungan Anak Dan Keluarga Berencana Jawa Barat - Syani, Mamay; Putra Nugraha, Reza; Ahmad Firdaus, Eryan (LPPM Universitas Nias Raya, 2024)
Domestic abuse is a social problem in Indonesia that always be inherent and not easy to deal with, the rate of domestic abuse exploded when pandemic happen in Indonesia. in West Java alone there already 2000 case about domestic abuse that already registered. This number can be pressed if society have the courage and awareness about domestic abuse among them, as a victim or as a witness of the abuse. This multimedia application was designed for facilitate the socialization process of domestic abuse in order to cultivate courage in society to report if they see someone they know is a victim of domestic abuse. So, an information multimedia application of domestic abuse public service advertisements with a case study at the West Java Women's Empowerment, Child Protection and Family Planning Office was created. The methodology used is Multimedia Development Life Cycle (MDLC) that have 6 stages (concept, design, material collecting, assembly, testing, and distribution). The , multimedia application of domestic abuse public service advertisements was designed according to users need obtained from observation and implemented using Adobe Animate CC 2019 with Action Script 3.0 programming language.the testing of this application is using black box testing method show that this application running smoothly and fit to what the user wants. The result of this testing show that the average of the testing result from 3 category (design, feature, and user satisfaction) with 12 test parameters is 4,39 (87,8%).